2020
DOI: 10.1039/c9qi01475f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and NMR study of trimethylphosphine gold(i)-appended calix[8]arenes as precursors of gold nanoparticles

Abstract: In this paper, the synthesis of gold(i)-calix[8]arene complexes from benzyloxycalix[8]arene is reported as well as their radiolytic reduction leading to gold nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
(29 reference statements)
0
16
0
Order By: Relevance
“…First, trimethylphosphine Au(I)-appended calix [8]arene containing eight and sixteen equivalents of gold (Au(I)-C8 and 2Au(I)-C8, Chart 1) were synthesised and characterised by 1 H and 31 P NMR spectroscopy. 6 We also showed that the radiolytic reduction of these complexes leads to the formation of small Au NPs homogeneous in size. This has prompted us to prepare bimetallic complexes with eight equivalents of gold and eight equivalents of silver, and to reduce them to produce alloyed bimetallic NPs.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…First, trimethylphosphine Au(I)-appended calix [8]arene containing eight and sixteen equivalents of gold (Au(I)-C8 and 2Au(I)-C8, Chart 1) were synthesised and characterised by 1 H and 31 P NMR spectroscopy. 6 We also showed that the radiolytic reduction of these complexes leads to the formation of small Au NPs homogeneous in size. This has prompted us to prepare bimetallic complexes with eight equivalents of gold and eight equivalents of silver, and to reduce them to produce alloyed bimetallic NPs.…”
Section: Introductionmentioning
confidence: 71%
“…The main aromatic resonances observed around 6.3 ppm for Au(I)-C8 disappear in favour of two broad signals around 5.9 and 6.5 with the addition of Ag(I)-(PPh 3 ) 2 revealing a lowering of the symmetry of the formed Au(I)Ag(I)-C8 complexes, as already noted in the case of the previously synthesised 2Au(I)-C8 complexes. 6 Moreover, in the case of Au(I)-Ag(I)-C8_R1, the spectrum shows more resolved peaks compared to Au(I)-Ag(I)-C8_R2 suggesting more rigid conformers. The presence of Et 3 N in excess in the case of the route R1 might account for such results possibly by hydrogen bonding between the acidic [H-N(Et 3 )] + and the free hydroxyl groups of the calixarene.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…1, 4), 24 antibacterial, anti-infectives, antprotozoal, antituberculosis, antitrypanosomiasis compounds 5,18,19,[25][26][27][28][29][30][31][32] . The phenanthridine ring systems are also used in lockable colorimetric fluorescence molecular switch, PET tracers, and in material science applications 4,15,22,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] .…”
Section: Introductionmentioning
confidence: 99%
“…47 The surface of MNPs has also been functionalized with macromolecules such as calixarenes, crown ethers and cyclodextrins due to the macrocyclic properties of these compounds which have a stabilizing effect of the entire entity along with the stabilization of the magnetic core. The unique host-guest type interactions and the variation in ring sizes and chemical groups thus make them attractive candidates for surface functionalization [48][49][50][51][52][53] .…”
Section: Introductionmentioning
confidence: 99%